Mutual excitation in eurozone sovereign CDS - Yacine Aït-Sahalia; Roger J. A. Laeven; Loriana Pelizzon (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2014)
We study self- and cross-excitation of shocks in the Eurozone sovereign CDS market. We adopt a multivariate setting with credit default intensities driven by mutually exciting jump processes, to capture the salient features observed in the data, in particular, the clustering of high default probabilities both in time (over days) and in space (across countries). The feedback between jump events and the intensity of these jumps is the key element of the model. We derive closed-form formulae for CDS prices, and estimate the model by matching theoretical prices to their empirical counterparts. We find evidence of self-excitation and asymmetric cross-excitation. Using impulse-response analysis, we assess the impact of shocks and a potential policy intervention not just on a single country under scrutiny but also, through the effect on cross-excitation risk which generates systemic sovereign risk, on other interconnected countries.
Keywords: C13; G12; 330; CDS; Sovereign risk; Systemic risk; Jumps; Feedback; Hawkes processes; Mutually exciting processes; Impulse-response